Needs analysis for developing critical reading: Perspectives from EFL undergraduates and teachers - Dongmei He; Asmaa AlSaqqaf (International Journal of Instruction, 2025)
Relevant literature revealed that critical reading presents a significant challenge for English as a Foreign Language (EFL) learners, especially non-English major undergraduates in China. Although critical reading is widely acknowledged as essential, its effective integration into EFL instruction remains inadequate. This study is an initial step in exploring strategies to address this gap. It aims to discover the need to develop critical reading skills from the perspectives of Chinese EFL non-English major undergraduates and EFL teachers. A sample of 386 non-English major EFL undergraduates and 82 EFL teachers participated in the study, with a Need Analysis Students’ Questionnaire (NASQ) and a Need Analysis Teachers’ Questionnaire (NATQ) used. Results revealed a congruency between learners and teachers, as both groups reported moderate levels of engagement—learners in their use of critical reading skill (M = 3.151) and teachers in implementation of critical reading instruction (M = 3.045). This study recommends designing modules that align teacher instruction with learner needs, developing critical reading skills from lower-level to progressively higher-level skills, and providing structured tasks within the skills development.